2023
DOI: 10.15177/seefor.23-19
|View full text |Cite
|
Sign up to set email alerts
|

Chemical and Energetic Properties of Seven Species of the Fabaceae Family

Federico Salazar-Herrera,
Luis Fernando Pintor-Ibarra,
Ricardo Musule
et al.

Abstract: In this work, the chemical compositions and energetic properties of the wood and bark of seven Fabaceae species were determined to evaluate their dendroenergetic potential. Chemical composition, elemental, proximate and heating value analyses were conducted. In addition, an ash microanalysis was performed. The obtained results varied as follows: cellulose (from 20.21% in Parkinsonia aculeate bark to 58.83% in Albizia plurijuga sapwood), hemicelluloses (from 8.81% in Eysenhardia polystacya heartwood to 23.71% i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 29 publications
0
3
0
Order By: Relevance
“…Carrillo et al [ 5 ], for example, reported the following percentages: hemicelluloses 16%, cellulose 45.7%, lignin 31.4%, and extractables 16%. In contrast, based on a fiber analysis by the Van Soest method [ 7 ] published these yields: hemicelluloses 14.09%, cellulose 45.35%, lignin 22.14%, extractables 16.72%, and ash 1.70%. The results of our work are only comparable with respect to cellulose, lignin, and ash, according to these references ( Table 1 ).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Carrillo et al [ 5 ], for example, reported the following percentages: hemicelluloses 16%, cellulose 45.7%, lignin 31.4%, and extractables 16%. In contrast, based on a fiber analysis by the Van Soest method [ 7 ] published these yields: hemicelluloses 14.09%, cellulose 45.35%, lignin 22.14%, extractables 16.72%, and ash 1.70%. The results of our work are only comparable with respect to cellulose, lignin, and ash, according to these references ( Table 1 ).…”
Section: Resultsmentioning
confidence: 99%
“…Because P. laevigata wood has an especially high amount of fixed carbon, it is a solid biofuel of good quality. The proximate analysis of the duramen of P. laevigata in a study using gravimetric methods obtained the following percentages: ash 1.70%, volatile matter 78.46%, and fixed carbon 19.83% [ 7 ]; while in their work, Martínez-Pérez et al [ 6 ] reported 1.24% of ash in the duramen of this species. In comparative terms, only the percentage of ash obtained in these two reports is comparable to the references consulted ( Table 1 ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation